Towards an ideal neonatal sepsis screen panel - A review - Gengaimuthu, Karthikeyan; Karthikeyan, Vaishni (Indian Journal of Child Health, 2017)
Neonatal sepsis is an important determinant of survival in the neonatal units. Early recognition and institution of antibiotic therapy is the key for successful treatment. Complete blood count and C-reactive protein are the ritualistic commonly used tests that aid the clinician in the initiation and stopping of antibiotic therapy. Procalcitonin at 24 h is useful in diagnosing early-onset neonatal sepsis (EOS). Interleukin 6 and CD 11? for EOS and CD 64 for late-onset sepsis are promising candidates for future sepsis screen panel as logistical issues like the cost factor rule out their routine use currently. We summarize the current available evidence on the use of these laboratory markers and the clinical sepsis score and suggest a practical guide for antibiotic therapy (initiation and duration of treatment) for the benefit of practicing pediatricians.